2015
DOI: 10.3852/14-298
|View full text |Cite
|
Sign up to set email alerts
|

Hymenochaetaceae from the Guineo-Congolian rainforest: three new species ofPhylloporiabased on morphological, DNA sequences and ecological data

Abstract: Four species are added to Phylloporia. Three species, originating from the western edge of the Guineo-Congolian rainforest in Gabon (central Africa), are described as new. Phylloporia afrospathulata sp. nov. forms seasonal, stipitate, solitary basidiomata emerging from soil, more likely connected to buried roots, and has broadly ellipsoid basidiospores. Phylloporia inonotoides sp. nov. forms seasonal sessile, soft basidiomata, solitary at the base of small-stemmed trees including Crotonogyne manniana (Euphorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…These are difficult to align confidently. Accordingly, most phylogenies were based on LSU sequences (Decock et al 2015;Yombiyeni et al 2015;Ferreira-Lopes et al 2016;Zhou 2016;Rajchenberg et al 2019;Wu et al 2019Wu et al , 2022. Although Phylloporia is shown to be monophyletic based on LSU sequences, the genus is composed of a non-trivial number of subclades (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These are difficult to align confidently. Accordingly, most phylogenies were based on LSU sequences (Decock et al 2015;Yombiyeni et al 2015;Ferreira-Lopes et al 2016;Zhou 2016;Rajchenberg et al 2019;Wu et al 2019Wu et al , 2022. Although Phylloporia is shown to be monophyletic based on LSU sequences, the genus is composed of a non-trivial number of subclades (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically by a monomitic to rarely dimitic hyphal system, absence of setal elements and small (< 6 µm long), subglobose to cylindrical, yellow, thick-walled, non-dextrinoid and frequently collapsed basidiospores. Nutritional strategies of Phylloporia species are not yet fully understood, it is known they cause white rot on different parts of living angiosperms, but relationships and effects on their host physiology have been rarely studied (Esquivel & Carranza, 1996;Yombiyeni et al, 2015). However, Phylloporia species have been cited as phytopathogens with high host-specialization (Valenzuela et al, 2011; describe their macroscopic and microscopic characteristics, DNA extraction was performed and the 28S rDNA (LSU) was amplified by PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou & Dai, 2012;Decock et al, 2015), although several species can be found to be saprophytic in dead aerial wood (Douanla-Meli et al, 2007), or terrestrial, connected to living/dead wood (Wagner & Ryvarden, 2002;Ipulet & Ryvarden, 2005;Yombiyeni et al, 2015). Additionally, Yombiyeni et al (2015) refer to the association between habit and the plant organ with the basidiomata in Phylloporia as the «morpho-ecologycal type», and stipitate basidiomata emerging from soil or associated to root had been named «P. spathulata» or «stipitate on root» morpho-ecological type (Ferreira-Lopes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed interest in Phylloporia was stimulated by Wagner and Ryvarden’s (2002) phylogenetic and morphological study in which they accepted 12 species. Since then, a number of new species have been described from Africa (Ipulet and Ryvarden 2005, Decock et al 2015, Yombiyeni et al 2015, Yombiyeni and Decock 2017), the Americas (Valenzuela et al 2011, Decock et al 2013, Ferreira-Lopes et al 2016) and Asia, especially China (Gafforov et al 2014, Cui et al 2010, Zhou and Dai 2012, Zhou 2013, 2015a, 2015b, 2016, Liu et al 2015, Chen et al 2017, Ren and Wu 2017). …”
Section: Introductionmentioning
confidence: 99%